If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 1 = -22 Reorder the terms: 1 + -7x = -22 Solving 1 + -7x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -7x = -22 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = -22 + -1 -7x = -22 + -1 Combine like terms: -22 + -1 = -23 -7x = -23 Divide each side by '-7'. x = 3.285714286 Simplifying x = 3.285714286
| 7(-1)+3y=2 | | t/3=5.2 | | cos(x)=-0.645 | | 10x+140=10x+20+x^2+2x | | cosx=-0.645 | | -45+3x=-60 | | ax+15=20 | | -45+3x=60 | | 1654x=16540 | | 5*x+y=4.74 | | 0.75x-0.5=x+1.3333 | | (X+2)(2x^2-x+3)=0 | | ln(x^2)=4.7 | | 11-2=60 | | 5x-23=-1 | | w/20=4 | | 5x-23=1 | | 5x-8=20-x | | s*6-20=154 | | 32x+8y=2080 | | ln(5-x)=2.4 | | (32x)+8(260-4x)=2080 | | (Xy+3)(xy-3)=0 | | (32x)+(260-4x)=260 | | 2x^2+40x-72=0 | | 300=20x+80 | | 10*h+7=77 | | X^2+7x+12=-32 | | 3n-(5p)+2n=10p | | f(x)=y^2+8x | | -6x-23=-41 | | u-9=9 |